Kemampuan Berpikir Kreatif Matematis Siswa melalui Pendekatan Matematika Realistis - Devi Anna Siregar; Laili Habibah Pasaribu; Lily Rohanita Hasibuan (Universitas Swadaya Gunung Djati, 2026)
Research on mathematics learning has largely emphasized procedural mastery, while the development of students' creative thinking skills, particularly in madrasah settings, has not received optimal attention. Furthermore, empirical evidence regarding the effectiveness of the Realistic Mathematics Approach (RMA) in improving junior high school students' creative thinking skills is still very limited. The purpose of this study was to investigate how the use of the RMA affects students' original thinking skills in mathematics learning. This study used a pre-experimental design with one experimental group and no control group. The subjects were one class of students from various majors at MTs Hubbul Wathan Aek Nabara. Data were obtained through creative thinking ability assessments given before and during the implementation of the RMA, and supplemented by observations of student activities and engagement in the learning process. The application of the RMA significantly improved students' creative thinking skills, according to the research findings. The magnitude of the effect of the application of the RMA was calculated using Cohen's d effect size based on the difference in the average pretest and posttest scores. The calculation results showed an effect size of 5.65, which is included in the very large effect category. This shows that the implementation of PMR has a very strong impact on improving students' creative thinking skills in the Two-Variable Linear Equation System. This improvement reflects flexibility of thinking, fluency in generating ideas, and the ability to use various problem-solving strategies. This finding provides a theoretical contribution to strengthening the role of AMR in developing higher-order thinking skills, as well as practical implications for teachers in implementing contextual and student-centered mathematics learning.